The art of moving things - Fairchild, Anna Della (My University, 1891)
Introduction: If we could look from the dippy heights of the swallow as it skims its way through the blue skies, we should see below us sunny hills and shady valleys dotted with fields of waving grain. Quick little villages would peep out from beneath the trees and towering cities with their whim of machinery and clang of bells would send up to our ears a murmur of busy life. Far out in the distant harbor the stately ships come sailing in, the little steamer puffs noisily into the dock while the wharf swarms with a surging crowd. All is peace and prosperity—all is life and energy. Who painted this beautiful picture! Was it Millet? Orr does the brilliant coloring denote Tumer’s masterhand? Oh no! Your voices give to those great artists a genius they never had. No hand but that which framed the world could paint so wonderful a scene. It is not only a picture – it is reality. It is nature with all her sway of sovereignty, with all her power of rule still within the bonds of man. Here is Nature’s power over man, man’s power over Nature—value and utility combined. “The rule by obeying Nature’s power,” says Tennyson.
Citation: Fairchild, Anna Della. The art of moving things. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: English; nature; Tennyson; Romantic; Theses; Manuscripts (documents)